2021
DOI: 10.1016/j.jds.2020.06.020
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory effect of topical antibiotics/antiseptics administration on bacterial growth in the open wound of the jawbone surgery: Randomized controlled, preliminary study

Abstract: Background/purpose TThe bone cavities after extirpation of cysts or tumor of the jawbone requires the insertion of gauze containing various antibiotics/antiseptics to minimize the risk of pain, bleeding, and surgical site infection (SSI). However, there have been few reports on the efficacy of topical administration of antibiotics/antiseptics to an open wound of the jawbone. To compare the inhibitory effects of topical povidone-iodine gel and tetracycline ointment on the jawbone wound bacterial gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…Tetracycline is a broad-spectrum antibiotic with activity against Gram-positive and Gram-negative aerobic and anaerobic bacteria that is usually prescribed for bacterial skin infection [ 22 ]. A topical tetracycline ointment was superior to a povidone-iodine gel in terms of inhibitory effects towards MRSA [ 23 ]. Hence, D. alatus twig extract (with concentrations of 20 and 40 mg/g; D20 and D40) and tetracycline (Tetra) emulgel formulations were prepared for comparison in the current study.…”
Section: Discussionmentioning
confidence: 99%
“…Tetracycline is a broad-spectrum antibiotic with activity against Gram-positive and Gram-negative aerobic and anaerobic bacteria that is usually prescribed for bacterial skin infection [ 22 ]. A topical tetracycline ointment was superior to a povidone-iodine gel in terms of inhibitory effects towards MRSA [ 23 ]. Hence, D. alatus twig extract (with concentrations of 20 and 40 mg/g; D20 and D40) and tetracycline (Tetra) emulgel formulations were prepared for comparison in the current study.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, gas impregnated with Tec antibiotic ointment is generally used in open wounds of the jawbone. [ 148 ] In a report by Ranjbar‐Mohammadi et al, [ 149 ] CS/PLA nanofibers containing Tec antibiotic were prepared by electrospinning method. The results showed that long‐term controlled release of Tec was effective in treating some chronic infections.…”
Section: Drugs In Wound Healingmentioning
confidence: 99%
“…C hronic refractory wound refers to a wound that is difficult to heal for various reasons. 1,2 There are many types and complex causes, and it is not clearly defined currently. It is usually identified as a chronic wound that cannot be reduced by 10% to 15% per week or by 50% for more than 1 month.…”
mentioning
confidence: 99%